Animals and Artificial Intelligence: Nonhumans as Moral Agents? - Baďurová, Barbora (Studia Ecologiae et Bioethicae, 2024)
There is a widely debated issue regarding the status and impact of exponentially growing artificial intelligence. The article deals with the problem of the moral agency of animals, and artificial intelligence. The author addresses several criteria for moral agents and tries to find the answer to the question of whether we can treat animals and AI as moral agents. The author uses mostly method of philosophical analysis and comparative method. The author claims that moral agency is not a necessary condition for moral status and doubts the practicality of attributing full moral agency to animals and AI. Moreover, claims that moral agency comes in degrees and different kinds and therefore we have to consider the complex nature of moral agency when dealing with moral actions. For instance, even human moral agents are not all on the same level of development as suggested not just by empirical evidence but also virtue ethics.